Intelligent system approaches to enhance knowledge management in organization: Preliminary study - Ariffin, Asma Hanee; Rahmat, Abdul Razak; Wan Ishak, Wan Hussain (Faculty of Information Technology, Universiti Utara Malaysia, 2004)
This paper presents a preliminary study which attempts to identify, the most adaptable methodology that can be utilized in order to develop Intelligent Knowledge Management Systems. It reveals the elements of Intelligent System to knowledge management in organization, as a preface to the sets of methodologies in AI.By using AI and understanding of human's needs, which is utilizing the workers' external strengths, these will support organizations in gaining competitive advantages in the global market.